2021
DOI: 10.1088/1361-665x/abd7e6
|View full text |Cite
|
Sign up to set email alerts
|

Research on energy consumption of fiber-reinforced fluidic soft actuators

Abstract: Fluidic soft actuators have drawn more and more research interest in recent years, but it is not clear on their behaviors of dynamical energy consumption, which is critical to power system design. To solve this problem, this work develops an analytical model of required energy including elastic potential energy and dissipated energy for fiber-reinforced fluidic soft actuators based on the theory of viscoelasticity. Since the parameters of soft material are difficult to obtain, the key parameters in the model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In general, soft pneumatic actuators are relatively low power consumption devices, as they rely on the stored energy in compressed air to generate motion, rather than relying on electrical or mechanical power sources [43][44][45][46].…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, soft pneumatic actuators are relatively low power consumption devices, as they rely on the stored energy in compressed air to generate motion, rather than relying on electrical or mechanical power sources [43][44][45][46].…”
Section: Applicationsmentioning
confidence: 99%
“…Holding the actuator in a required position consumes energy and power continuously. Previous works required constant pressure to hold the actuator in the required position for a long time [43,44]. These research works showed how much energy and power were consumed to activate the actuators.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parts made of silicone rubber are fabricated by casting method, and the chambers and the silicone tubes inserted at the top are spliced using silicone adhesive (Ease Release 200, Smooth-on, USA). 36,37 The design length of the single-section soft robotic arm is 130 mm and the outer diameter is 25 mm.…”
Section: Hydraulic Soft Robotic Armmentioning
confidence: 99%